Student Learning Disciplines in Class III Online Learning - Andrianingsih, Rosita Talia; Busyairi, A. (Universitas Negeri Semarang, 2021)
This study aims to describe student learning discipline in online learning, as well as describe the factors that lack student learning discipline in online learning. This study uses a qualitative approach with a descriptive type. Data collection techniques were carried out by interviews, observations, documentation and field notes regarding student learning discipline in online learning for class III. Researchers conducted interviews with third grade teachers, students and parents. Data analysis was carried out before and after in the field. Before in the field, it was carried out by conducting pre-research, while after in the field, data analysis was carried out using Miles and Huberman. The results showed that parents and teachers applied discipline with punishments, regulations, threats, warnings. However, online learning is still considered less effective for students of SD Negeri Karangwono 01. The factors for the lack of student learning discipline are boredom in students, difficulty in getting signals for online learning, less than optimal parental assistance time, and lack of understanding of students in learning. learning materials.Keywords: Student Learning Discipline, Online Learning